Interpretability of Attention Mechanisms in a Portuguese-Based Question Answering System about the Blue Amazon - Spindola, Stefano; José, Marcos Menon; Oliveira, André Seidel; Cação, Flávio Nakasato; Cozman, Fábio Gagliardi (Anais do Encontro Nacional de Inteligência Artificial e Computacional (ENIAC), 2021)
The Brazilian Exclusive Economic Zone, or the "Blue Amazon", with its extensive maritime area, is the primary means of transport for the country's foreign trade and is important due to its oil reserves, gas and other mineral resources, in addition to the significant inﬂuence on the Brazilian climate. We have manually built a question answering (QA) dataset based on crawled articles and have applied an off-the-shelf QA system based on a fine-tuned BERTimbau Model, achieving an F1-score of 47.0. More importantly, we explored how the proper visualization of attention weights can support helpful interpretations of the system's answers, which is critical in real environments.